SISTEM PENGELOLAAN DANA ZAKAT DI BAITUL MAL ACEH SINGKIL MENURUT PANDANGAN HUKUM ISLAM - fasya, fasya (IAIN Langsa, 2017)
This research is based on Law Number 23 of 2011 on the Management of Zakat which states that the management of Zakat must be in accordance with Islamic Shari'ah, convey, benefit, justice, legal certainty, integrated, and accountability. This research uses field research. The researcher interviewed directly with the administrators of Baitul Mal Aceh Singkil and completed with observation and documentation. The results of the research in Baitul Mal Aceh Singkil show that 1. The management of Zakat in Baitul Mal Aceh Singkil is done by several stages of planning that is the first way of Collection of Zakat, second distribution of Zakat fund, third, supervision and coaching, and evaluation of each programs that have 2. 2. Distribution is adjusted based on general interpretation of the meaning of fi sabilillah, because in particular the Qur'an and Ijma 'do not want any new group of Zakat recipients other than 8 main groups.